Efforts to Prevent COVID-19 by Applying Physical Distancing, Handwashing Behavior and Vegetable Fruit Consumption Patterns in Indonesia - Ade SaputraNasution; Muh ZulAzhri Rustam; Fakhrurradhi Luthf; Nanda Novziransyah; Muchti YudaPratama; Dwi Helynarti Syurandhari; Fitriani Pramita Gurning (Institute of Medico-legal Publications Pvt Ltd, 2021)
The phenomenon of the outbreak Covid-19 pandemic in a number of countries, including Indonesia. This condition not only affects the condition of a country, hinders social interaction among community, and also has been impact on the health condition of every human being. To avoid the wider spread of Covid-19, the Indonesian government adopted a policy of social distancing and physical distancing in the form of staying at home, working from home, studying, and worshiping at home.The research’s design used Analytical Observational with Cross Sectional Study design. The independent variables of this study are the application of physical distancing, the application of hands washing behavior and consumption pattern of fruits and vegetables. The amount of sampling in this study were 109 respondents spread across Bogor Regency, West Java using accidental sampling’s and analyzed using chi-square. The results of the study illustrate that efforts to prevent Covid-19 by implementing physical distancing, hands washing behavior and vegetables fruits consumption patterns can reduces the risk of being exposed to Covid-19 in Indonesia. The Indonesian people must apply the Covid-19 prevention appeal that has been set by the government to reduce the spread of Covid-19 in Indonesia.